Gut microbiota signatures of the three Mexican primate species, including hybrid populations - Diego Zubillaga-Martín; Brenda Solórzano-García; Alfredo Yanez-Montalvo; Arit de León-Lorenzana; Luisa I. Falcón; Ella Vázquez-Domínguez (PLoS ONE, 2025)
Diversity of the gut microbiota has proven to be related with host physiology, health and behavior, influencing host ecology and evolution. Gut microbial community relationships often recapitulate primate phylogeny, suggesting phylosymbiotic associations. Howler monkeys (Alouatta) have been a model for the study of host-gut microbiota relationships, showing the influence of different host related and environmental factors. Differences in life-history traits and feeding behavior with other atelids, like spider monkeys, may reveal distinct patterns of bacterial gut communities, yet few wild populations have been studied; likewise, gut microbiota studies of hybrid populations are mostly lacking. We analyzed diversity and abundance patterns of the gut microbiota of wild populations of the three Mexican primates Ateles geoffroyi, Alouatta palliata and A. pigra from different regions across its distribution in the country, including sympatric localities and the Alouatta hybrid zone. Interspecific differences in gut microbial diversity were higher than intraspecific differences, concordant with phylosymbiosis. Ateles harbored the more differentiated diversity with a major presence of rare taxa, while differences were less strong between Alouatta species. Hybrids had a microbial diversity in-between their parental species, yet also showing unique microbe taxa. Genetic distances between Alouatta individuals correlated positively with their gut microbial dissimilarities. Results show that interspecific and intraspecific overall diversity, abundance and composition patterns are affected by environment, geographic distribution and host genetics. Our study provides the first comprehensive study of gut microbiota of the three Mexican primates and hybrid populations.